The Integration of Logical Analysis into the Istinbāṭ Method of Islamic Jurisprudence - Putri, Nur Amelia; Rizki, Andriani Pratita; Rahmawati, Irma Widya; Millatillah, Mu'izzatu; Sulastri, Galena Astuty Sri; Azizah, Ma'rifatul; Kurniawan, Taufiq (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Islamic law is a legal system based on divine revelation. However, Islamic law's viability within modern contexts is profoundly dependent upon the engagement of human rationality and logical reasoning. These two components constitute essential mechanisms for elucidating the implications of Sharia texts, thereby ensuring that Islamic jurisprudence remains aligned with societal evolution and historical advancement. Together with rapid development in science and technology, such as the emergence of financial technology (fintech), bioethics, and artificial intelligence, Islamic jurisprudence confronts emergent dilemmas not explicitly delineated in the Quran or Hadith. That necessitates renewal within the methodology-in terms of how to bring the revealed and the rational together through the mechanism of istinbāṭ al-aḥkām. This study seeks to investigate the function of logic within the structure of Islamic jurisprudential methodology, as a special focus on implementation of qiyās., or legal analogy, and ta'līl, or causal reasoning, as types of legal rationalization based upon revelationThis research employs a descriptive qualitative methodology, utilizing library-based investigation. Data derived from six pertinent scholarly journals were subjected to a descriptive-comparative analysis to discern the parallels and divergences in the perspectives of classical and modern scholars regarding the methodology of Islamic legal deduction.The findings identify qiyās and ta‘līl as epistemological bridges between divine revelation and social reality. With a more rational approach, the philosophical and adaptive aspects of Islamic law are revealed, where the proper contextual application of Islamic law should respect divine principles.